Isle of Islay - Nature Observatory - Zhang, Zhen (Writingplace, 2018)
This graduation project is a social critique against the overrule of rationality over humanity, a frustrated plea for more emotional capacity (for love and nature) within (or beyond) a rational world. To overcome the conditions and paradox described above, I have developed various fictive concepts or utopias. The project here is one of such concepts, and perhaps also a radical and pessimistic one. The protagonist takes his frustration with an escapist attitude, leaves his city behind and tries to find his joy and purpose of life in a natural and prescientific environment. He arrives at a faraway island in Scotland, where natural elements, not rational human beings, are the dominating force. I designed various instruments or observatories for the modern man to get in touch with what he yearns for – nature: through folklores and tales he regains a prescientific eye; through the instruments, he experiences the varied elemental existence of nature – sun, moon, stars, water, fire, wind, waves . . . During this project I got inspiration from reading, writing and collecting. Travel logs written by English scholars, who travelled to Scotland in the eighteenth and nineteenth centuries, as well as folklore and tales of the Scottish islands were great inspirations; like a time machine, these words took me a few hundred years back to a prescientific state of mind.